Enhancing health and wellness by, for and with Indigenous youth in Canada: a scoping review - Udoka Okpalauwaekwe; Clifford Ballantyne; Scott Tunison; Vivian R. Ramsden (BMC, 2022)
Abstract Background Indigenous youth in Canada face profound health inequities which are shaped by the rippling effects of intergenerational trauma, caused by the historical and contemporary colonial policies that reinforce negative stereotypes regarding them. Moreover, wellness promotion strategies for these youth are replete with individualistic Western concepts that excludes avenues for them to access holistic practices grounded in their culture. Our scoping review explored strategies, approaches, and ways health and wellness can be enhanced by, for, and with Indigenous youth in Canada by identifying barriers/roadblocks and facilitators/strengths to enhancing wellness among Indigenous youth in Canada. Methods We applied a systematic approach to searching and critically reviewing peer-reviewed literature using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews [PRISMA-ScR] as a reporting guideline. Our search strategy focused on specific keywords and MeSH terms for three major areas: Indigenous youth, health, and Canada. We used these keywords, to systematically search the following electronic databases published in English between January 01, 2017, to May 22, 2021: Medline [Ovid], PubMed, ERIC, Web of Science, Scopus, and iportal. We also used hand-searching and snowballing methods to identify relevant articles. Data collected were analysed for contents and themes. Results From an initial 1695 articles collated, 20 articles met inclusion criteria for this review. Key facilitators/strengths to enhancing health and wellness by, for, and with Indigenous youth that emerged from our review included: promoting culturally appropriate interventions to engage Indigenous youth; using strength-based approaches; reliance on the wisdom of community Elders; taking responsibility; and providing access to wellness supports. Key barriers/roadblocks included: lack of community support for wellness promotion activities among Indigenous youth; structural/organizational issues within Indigenous communities; discrimination and social exclusion; cultural illiteracy among youth; cultural discordance with mainstream health systems and services; and addictions and risky behaviours. Conclusion This scoping review extracted 20 relevant articles about ways to engage Indigenous youth in health and wellness enhancement. Our findings demonstrate the importance of promoting health by, and with Indigenous youth, by engaging them in activities reflexive of their cultural norms, rather than imposing control measures that are incompatible with their value systems.